A formação interdisc iplinar de professores: um encontro com Paulo Freire - Celia Maria Haas (EccoS – Revista Científica)
The inquiries are concerned with the possibilities of formation and learning that occur taking as basis the interdisciplinary pedagogical project, constructed in partnership with teachers, students and some times, with the Institution. Thus, this text suggests a reflection on the construction of the pedagogical project of teachers formation, in a continuous dialogue with Paulo Freires thought, because this project detaches that the commitment with this formation needs to be showed in programs that make possible the construction of new ways to teach and learn.